Severe bone marrow suppression following single-dose methotrexate treatment for ectopic pregnancy - Dündar, Betül; Dinçgez Çakmak, Burcu; Özgen, Gülten; Ketenci Gencer, Fatma; Aydın Boyama, Burcu (The European Research Journal, 2017)
Methotrexate is associated with multisystem side effects which depend on the dosage, route of administration and length of treatment. Bone marrow suppression is a very rare but one of the most mortal complications. A case of severe bone marrow suppression following single dose methotrexate for ectopic pregnancy was presented in this study. A 33-year-old woman, diagnosed as ectopic pregnancy, was given single-dose intramuscular methotrexate of 50 mg/m². On 10th day patient was admitted with lethargy, irritability, vomiting, hematemesis, diarrhea, oral mucositis and skin rash. Laboratory findings revealed severe bone marrow suppression. Supportive treatment together with antibacterial/ antifungal drugs and granulocyte colony stimulating factors were administered. On the 3rd day of treatment, mucositis and oral intake began to improve. After 1 week complete blood count was normal. Methotrexate may have mortal clinical consequences even with very low doses. Therefore, a careful patient history for patient selection and closer clinical follow-up are essential.